Respuesta :

Answer: 11

=========================

Explanation:

To find the inverse, or f^-1 of a function, you first replace the y= 6x-4 with x=6y-4

Finding the inverse from here is basically just finding y in terms of x.

1) x=6y-4
2) x+4=6
3) (x+4)/6= y

y= (x+4)/6 is now your f^-1.

Now that you have your inverse, replace 62 with your x in y=(x+4)/6

1) (62+4)/6
2) 66/6
3) 11

Therefore, f^-1(62)= 11

Hope this helps :)

Step-by-step explanation:

swap the variables:

y=6x−4 becomes x=6y−4.

Now, solve the equation x=6y−4 for y.

y=x+46 is the inverse function

f^-1(62)

substitude x=62

y=x+46

y= 62+46

y=108

f^-1(62)=108

brainliest please~

ACCESS MORE